2019
DOI: 10.14735/amko2019109
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Circulating Microparticles in Patients with BCR/ ABL Negative Myeloproliferative Neoplasm – a Pilot Study

Abstract: Background: Microparticles (MPs) are small (0.1-1 μm) cell-derived vesicles released during activation or apoptosis, with a surface-exposed phosphatidylserine along with antigens indicat ing the cellular origin. The level of MPs is known to be elevated in thromboembolic dis eases and malignancies; it is believed that MPs are not only amplify ing but can also initiate the thrombogenesis processes. BCR/ ABL negative myeloproliferative neoplasms (MPNs) are clonal haematopoietic dis eases, which include polycythem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…After we excluded the irrelevant manuscripts based on the screening of their titles and abstracts ( n = 81), we examined the full texts of 33 manuscripts. Finally, after we applied the exclusion and inclusion criteria, 27 original articles were included in this review [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After we excluded the irrelevant manuscripts based on the screening of their titles and abstracts ( n = 81), we examined the full texts of 33 manuscripts. Finally, after we applied the exclusion and inclusion criteria, 27 original articles were included in this review [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The analyzed studies investigated the levels of cell-free DNA ( n = 1), extracellular vesicles ( n = 7), microparticles ( n = 14) or circulating endothelial cells ( n = 5) levels in MPNs. Flow cytometry was by far the most employed method of detection ( n = 23) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among myeloproliferative neoplasms (MPNs), due to their overlapping features, polycythemia vera, essential thrombocythemia (ET), and primary myelofibrosis have been traditionally grouped into a unique category of Ph − classical MPNs [94]. One of the main problems of MPN patients is the high risk and incidence of thrombosis which affects survival, quality of life, and life expectancy [96].…”
Section: Myeloproliferative Neoplasmsmentioning
confidence: 99%
“…In particular, MPs derived from different cell sources, such as platelet-, erythrocyte-, red blood cell-, and endothelial-MPs, were found significantly augmented in MPN patients compared with healthy subjects. Interestingly, blood MP levels are positively correlated with the occurrence of thrombotic complications in MPN patients [96][97][98]. In addition, another recent study analyzed plasma levels of tissue factor positive-MPs from 59 MPN patients at diagnosis and during clinical course of disease, and showed that their procoagulant activity was significantly higher in patients suffering thrombotic events than in patients without such events.…”
Section: Myeloproliferative Neoplasmsmentioning
confidence: 99%